Wastewater deodorization methods at wastewater treatment plants - E. S. Glushchenko; A. A. Kadyseva (Архитектура, строительство, транспорт)
The article presents a review of existing methods for reducing gases’ emissions with specific unpleasant odors during the process of wastewater and sludge treatment at wastewater treatment plants. The review is based on the Russian and foreign research in the period from 2000 to 2020. The article considers advantages and disadvantages of the main methods for reducing the concentration of pollutants in the air near treatment plants.